Analisis Belanja Daerah dalam Penanggulangan Banjir Rob: Studi Kasus Pengeluaran Pemerintah Kota Semarang Tahun 2022-2024 - Adinda Eka Fadilah; Fabima Rohmatimminallohi Lintalahum; Revienda Anita Fitrie; Eva Hany Fanida (Pustaka Digital Indonesia, 2026)
Flooding caused by tidal inundation (rob flood) in Semarang City has become a chronic urban coastal problem driven by land subsidence, sea level rise, and increasing environmental pressure in coastal areas. This study aims to analyze the allocation, implementation, and effectiveness of local government spending in flood mitigation efforts during the 2022–2024 period. The research employed a qualitative descriptive approach using secondary data obtained from Budget Realization Reports (Laporan Realisasi Anggaran/LRA), Government Agency Performance Reports (Laporan Kinerja Instansi Pemerintah/LKjIP), Regional Revenue and Expenditure Budget (APBD) documents, and other official government reports. The findings show that the budget realization rate of Semarang City remained consistently high, reaching 93.85 percent in 2022 and percent in 2023, while the Regional Disaster Management Agency (BPBD) achieved realization rates of up to 95.99 percent. These figures indicate strong administrative and procedural performance in regional financial management. However, high budget absorption has not automatically translated into substantial effectiveness in reducing tidal flood risk. Regional spending remains dominated by structural and short-term approaches, such as drainage improvement, pump operations, emergency response, and infrastructure maintenance, whereas long-term preventive investment and integrated risk management remain limited. In addition, the absence of a specific budget classification for tidal flood mitigation within the LRA complicates the identification and evaluation of related expenditures across sectors. Empirically, several coastal areas still experience periodic inundation, particularly in Genuk and North Semarang. This study concludes that regional spending on tidal flood mitigation in Semarang City during 2022–2024 was administratively effective but substantively not yet optimal in producing significant and sustainable risk reduction. Therefore, a more preventive, integrated, and long-term risk-based policy approach is required to improve the effectiveness of regional expenditure in coastal disaster mitigation.